Comparative Analysis of Flexible Road Pavements Design Methods Applied in RA - Vardanyan, Yegiazar; Gyulzadyan, Hakob (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The comparative analyzes of standart cods currently used in the Republic of Armenia for flexible road pavements design is presented: instructions VSN -46-83, industry standards ODN 218.046-01, national standards PNST 265-2018, PNST 542-2021 and the AASHTO method. The features of assessment by these methods of traffic loads, overall stiffness of the pavement, reliability characteristics, serviceability factors, characteristics of the subgrade soil and materials of pavement layers, are compared. For RA conditions, using the above methods, comparative analyzes of pavement structures with different traffic levels and different strengths of the subgrade were carried out. According to these analyses, in the case of roads with high traffic levels, the most rigid structures are obtained in the case of design by the standard ODN 218.046-01. In the case of design by other post-Soviet standards, comparable results were obtained. The results obtained by the AASHTO method are also close. For roads of medium and low traffic levels in the case of design by ODN 218.046-01, PNST 265-2018 and PNST 542-2021, comparable results are obtained, while, in almost all cases, shear stability checks become decisive. The structures obtained as a result of design by VSN-46-83 and AASHTO AASHTO have the lowest rigidity and are close to each other for most design cases.